A STUDY ON MASTERING ENGLISH PASSIVE VOICE IN SIMPLE PRESENT, SIMPLE PAST AND SIMPLE FUTURE TENSES BY THE GRADE 12TH STUDENTS OF ESCOLA SECUNDARIA PUBLICA NOBEL DA PAZ, DILI TIMOR-LESTE IN ACADEMIC YEAR 2020 - Augusta Assunção; Adelaide da Costa Lay; Atanasio A. Gusmão Freitas Belo A. Gusmão Freitas Belo (Postgraduate School, Universitas Nusa Cendana, 2020)
This study is entitled “A study on Mastering English Passive Voice (simple present, simple past and simple future tense) by the Grade 12 Students of Escola Secundária Pública Nobel da Paz, Dili Timor-Leste in the School Year 2020”. The aim of this study is to find out whether or not the grade 12 students master English passive voice as well as to know their mastery level. The population of this study is all the grade 12 students that consisted of four classes and only 30 students who were selected randomly as the sample or respondents. The instrument used for the data collection is a questionnaire in which it comprisis 30 numbers of questions. The methods used in this research are qualitative and quantitative approaches.